Exposure to magnetic fields estimated from last job held in an electrical utility in Québec, Canada: a validation study. Issue 5 (May 1996) - Baris, D; Armstrong, B G
Abstract : OBJECTIVES: To investigate how closely the variables of exposures to magnetic fields based on the last job held in an electrical utility in Québec, Canada, compared with those based on the workers' entire employment history with the company. METHODS: In large cohort studies, the last job held is often used to assign exposure to the study subjects. Exposure was assigned in this way for a mortality study of a cohort of electrical utility workers in Québec. For the present study, a sample of the cohort was used to compare the exposure estimates obtained from the last job with those obtained from full work histories. RESULTS: The correlations between indices based on the last job and on all jobs varied between 0.75 and 0.78. The mean was slightly lower when only the last job was used. The last job was particularly good in identifying the most highly exposed people (for the exposure cut off point of 90th percentile for the last job and for all jobs, sensitivity = 0.69, specificity = 0.97, kappa = 0.66). The results suggest that although not all workers starting in highly exposed jobs stayed in them, it seemed that the workers who ended their working life in highly exposed jobs had stayed in these jobs throughout their working life. CONCLUSION: The results indicated some (but not catastrophic) loss of information when estimates of exposure were based on the last job only.